Assessing predictors for health insurance purchase among Malaysian public sector employees - Abdul Rahim @ Abdul Wahab, Husniyah; Sulaiman, Norhasmah; Othman, Mohamad Amim (Springer International Publishing, 2017)
Challenges are faced by individuals in making financial decisions throughout their life to be financially well. Managing risk such as health risks may incur high cost to remain healthy. Individuals make decisions on having protection against health risks in the long run which depends on several factors. This study focused on the behavioral aspects of finance which attempts to assess factors predicting health insurance purchase among Malaysian public sector employees. The likelihood of personality and health risks factors in predicting health insurance purchase were determined. Multistage random sampling based on four zones in Peninsular Malaysia was utilized to sample 500 respondents from four states. Selected departments in the states were contacted prior to the data collection for their consent. Respondents identified by liaison officers in each department were given self-administered questionnaires resulting in 356 usable questionnaires. Apart from socioeconomic characteristics and health insurance purchase, data on investment, personality and health status were collected. Personalities measured were self-esteem, risk-averse and future-orientation, while health risks were measured through health status using SF-36. The primarily measures and the aggregate measures of health were analyzed in two separate binomial logistic regressions where both analyses revealed that income was the strongest predictor as compared to investment activity or self-esteem. None of the indicators for health risks was found to be significant in predicting health insurance purchase. Both models were justified as fit by being moderately correctly classified and were more than 25% improvement over the chance accuracy rate. It is concluded that the decision on protection against health risks using health insurance is not based on their health risks instead the decision depends more on their income. As these are employees in the public sector, it may reflect high reliance on the government health service. Nevertheless, the public sector is considered as a potential market for health insurance industry.